Why do individuals choose self-employment? - Christopher Dawson; Andrew Henley; Paul L. Latreille (Institute for the Study of Labor (IZA), 2009)
This paper undertakes an analysis of the motivating factors cited by the self-employed in the UK as reasons for choosing self-employment. Very limited previous research has addressed the question of why individuals report that they have chosen self-employment. Two questions are addressed using large scale labour force survey data for the UK. The first concerns the extent to which the self-employed are self-employed out of necessity, opportunity, lifestyle decision or occupational choice. The second concerns the extent to which there is heterogeneity amongst the self-employed on the basis of the motivations that they report for choosing self-employment. Factor analysis reveals a number of different dimensions of entrepreneurship on the basis of stated motivation, but with no evidence that being 'forced' into entrepreneurship through economic necessity is a significant factor. Motivation towards entrepreneurship is therefore highly multidimensional. Multivariate regression analysis is employed using a method to control for self-selection into self-employment. This reveals significant differences between men and women, with women concerned more with lifestyle factors and less with financial gain. Market-directed 'opportunity' entrepreneurship is more strongly associated with higher educational attainment. Those joining family businesses appear not to value prior educational attainment. Public policy to promote entrepreneurship therefore needs to be tailored carefully to different groups.
urn:nbn:de:101:1-20090210136
Keywords: L26; J24; 330; Self-employment; entrepreneurship; motivation; occupational choice; Berufswahl; Selbstständige; Unternehmer; Motivation; Großbritannien